Estratigrafia, Petrografia e Gênese da mineralização de Potássio em Siltitos Verdes(Verdetes) do Grupo Bambuí na região de São Gotardo, Minas Gerais - Debora Silvano Moreira (2015)
The extensive green siltstones units that occur in the São Gotardo region, Minas Gerais state, known as verdetes. The verdetes belong to the Bambuí Group within the Serra da Saudade Formation and can be used as a source of potassium fertilizer in agriculture. This paper presents the mineralogy, petrography and stratigraphy of the green siltstones and analyzes the vertically spreading of potash. The mineralogy was analyzed using X-ray diffraction, optical mineralogy, electron microprobe and scanning electron microscope. The results showed the verdete contains glauconite (40-80%), K-feldspar (10-15%), quartz (10-60%), muscovite (5%), biotite (2%), titanium oxide and manganese oxide (<1%), goethite (<1%) and barium phosphate and rare-earth elements phosphate (trace). Mineralized zones of potential potash fertilizer have K2O grades between 8 and 12%, thickness up to 50 m and are associated to the glauconite units. The glauconite is authigenic and is related to a depositional environment with a low sedimentation rate. The verdete have resulted from a high level flooding event in the Bambuí Basin. The sedimentary provenance is from supracrustal felsic elements on continental margin environment with acid magmatic arc (foreland basin).